1983
DOI: 10.2136/sssaj1983.03615995004700020016x
|View full text |Cite
|
Sign up to set email alerts
|

An Agar Plate Method for Rapid Screening of Rhizobium for Tolerance to Acid-Aluminum Stress

Abstract: An agar plate method has been developed for the rapid, preliminary screening of large numbers of rhizobia for tolerance to acidity and aluminum (acid-Al). Media containing pH indicators are used, and distinguish true tolerance from cases where growth depends on a previous pH shift. Strains which were highly tolerant or sensitive to acid Al on agar behaved similarly in defined liquid media. Strains that formed dry, pinpoint colonies were more sensitive to acid-AI than those that formed large, gummy colonies.Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 6 publications
3
32
0
3
Order By: Relevance
“…Both studies followed the methods described by Ayanaba et al (1983). In the present studies, it was found that the addition of Al decreased the pH of the media, similar to the studies of Ayanaba et al (1983). It was found, for example, that increases of Al from 0 mM Al to 500 mM Al decreased pH from 5.50 to 5.0±0.04.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Both studies followed the methods described by Ayanaba et al (1983). In the present studies, it was found that the addition of Al decreased the pH of the media, similar to the studies of Ayanaba et al (1983). It was found, for example, that increases of Al from 0 mM Al to 500 mM Al decreased pH from 5.50 to 5.0±0.04.…”
Section: Resultssupporting
confidence: 87%
“…The most likely hypothesis to explain the differences between those results and ours is the difference in the final pH of the defined medium. Both studies followed the methods described by Ayanaba et al (1983). In the present studies, it was found that the addition of Al decreased the pH of the media, similar to the studies of Ayanaba et al (1983).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…To alleviate these constraints selection of crops and production of transgenic plants that are Al-tolerant have been attempted recently. For the source of genes to produce transgenic plants, although Al-resistant microorganisms could be used, studies on Al-resistant microorganisms and genes have been carried out only in Rhizobia (Ayanba et al 1983;Johnson and Wood 1983;Flis et al 1993).…”
mentioning
confidence: 99%